Multi-energy calibration in plasma emission spectrometry: elemental analysis of animal feeds - Cora Jofre, Florencia; Barros, Ariane I.; Nóbrega, Joaquim A.; Savio, Marianela (Frontiers in Analytical Science, 2025)
This study evaluates the effectiveness of Multi-Energy Calibration (MEC) for multielemental analysis in animal feeds using plasma-based optical emission spectrometry (ICP-OES and MIP-OES). The aim was to improve accuracy in detecting essential minerals by overcoming matrix interferences that affect instrumental techniques. Swine feed samples from different growth stages were analyzed, focusing on essential minerals for animal health and productivity, such as Ca, Co, Cu, Fe, K, Mg, Mn, Na, P, and Zn. The MEC strategy utilizes multiple wavelengths per element, reducing calibration complexity and enhancing accuracy by using only two calibration solutions per sample. Results demonstrate that MEC improves recoveries (80%–105%) when compared to traditional external calibration (EC). The limits of quantification (LOQs) ranged from 0.09 mg kg⁻1 for Mn to 31 mg kg⁻1 for Ca and Na using MEC-ICP-OES, and from 0.08 mg kg⁻1 for Mn to 354 mg kg⁻1 for P using MEC-MIP-OES. For EC, they ranged from 0.4 mg kg⁻1 for Co to 195 mg kg⁻1 for K with ICP-OES and from 2.0 mg kg⁻1 for Mg to 607 mg kg⁻1 for Fe with MIP-OES. MEC provides high precision and matrix-matching capabilities. This makes MEC a reliable method for complex feed matrices, supporting more accurate feed formulations to ensure optimal livestock nutrition.